Peran Roh Kudus Sebagai Pandangan Dalam Kehidupan Orang Percaya (Pneumatologi) - Nopriadi Nopriadi; Ophilia Lindy Agrecia; Rohit Rohit; Sarmauli Sarmauli (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
The doctrine of the Holy Spirit or pneumatology is an important pillar in Christian theology which includes an understanding of the person, nature and work of the Holy Spirit as part of the Holy Trinity. This study highlights various aspects of the doctrine of the Holy Spirit in the Christian tradition, both in the Old and New Testaments, which identifies the role of the Holy Spirit as a helper, comforter, and source of divine truth and wisdom. This research uses a qualitative-descriptive approach with content analysis techniques, where main themes such as the characteristics, designations and functions of the Holy Spirit are analyzed from various literary sources. The results of the study show the importance of understanding the presence of the Holy Spirit in the lives of Christians, where the Holy Spirit acts as a source of spiritual strength that strengthens people to live lives that are faithful to the teachings of Christ. It is hoped that this research can contribute to the development of theological thinking related to pneumatology and broaden readers' insight into the meaning and function of the Holy Spirit in the Christian faith.